Hubungan Karakteristik Ibu dan Dukungan Sosial Terhadap Pemberian Asi Eksklusif pada Ibu Menyusui di Puskesmas Datuk Bandar Kecamatan Datuk Bandar Kota Tanjungbalai Tahun 2024 - Ruhil Dwi Cahyani; Parningotan Simanjuntak; Tetti Seriati Situmorang; Ninsah Mandala Putri Sembiring (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Wrong perceptions regarding exclusive breastfeeding can influence exclusive breastfeeding. An example is insufficient breast milk production. This reason is the main reason mothers do not breastfeed exclusively. In this case, the mother feels that her breast milk is not enough, with various complaints such as the breasts getting smaller, the breast milk becoming thinner, the baby crying more often and asking to be breastfed more often (Walyani, 2015). This research aims to determine the relationship between maternal characteristics and social support on the provision of exclusive breast milk to breastfeeding mothers at the Datuk Bandar Community Health Center, Datuk Bandar District, Tanjungbalai City in 2024. This type of research is research with a cross-sectional design. The population and sample were all breastfeeding mothers at the Datuk Bandar Community Health Center, Datuk Bandar District, Tanjungbalai City in 2024 in May-June, as many as 39 people using the total sampling technique using the Chi Square statistical test. There is no significant relationship between age and exclusive breastfeeding. There is a significant relationship between education level and exclusive breastfeeding. There is a significant relationship between work and exclusive breastfeeding. There is no significant relationship between social support and exclusive breastfeeding at the Datuk Bandar Community Health Center, Datuk Bandar District, Tanjungbalai City in 2024